Biochemical Screening of Penaeus vannamei Shell Waste by Liquid Chromatography-Tandem Mass Spectrometry - Jayalakshmi, M.; Vanitha, V.; Pushpabharathi, N. (Asian Journal of Chemistry, 2018)
Marine environment is a progressive route for the attainment of natural novel drugs. Substantially they are of secondary metabolites. This study is about the utilization of marine shrimp shell waste for the identification of unrevealed bioactive compounds with its pharmacological activity by LC-MS method. Biochemical screening of Penaeus vannamei shell waste revealed the presence of various bioactive compounds like arecoline which possess antibacterial activity, oleamide which has potent anti-inflammatory activity, desethylchloroquine which reports the antiplasmodial activity, dodecanamide which shows antibacterial property, C17 sphinganine which exhibits antimicrobial function and also the identification of 11-α-acetoxykhivorin which is a rare limonoid khivorin compound. This work is the first report concerned with the screening of biochemical components present in the ethanolic extract of Penaeus vannamei shell wastes by LC-MS method. It was concluded that Penaeus vannamei shrimp shell contains numerous bio compounds with high medicinal values which can be isolated and utilized in rational methods in future for the discovery of innovative drugs.